Turko-Tatar Population of Tomsk Province at End of 19th Century (First General Census of 1897) - Z. A. Tychinskikh (Научный диалог)
The historical-demographic and socio-cultural characteristics of the Tatar population of the Tomsk province at the end of the 19th century are presented. The ethno-demographic and urbanization processes that took place during this period are considered on the basis of the materials of the First General Census of the Russian Empire in 1897. The class, professional structure of the Tatar population of the province is described. Particular attention is paid to the problem of ethnic differentiation of the indigenous Turkic-Tatar population of the region. The scientific novelty of the study is largely determined by the poor knowledge of the issue. The relevance of the study is due to the need for further study of the stages and factors of the formation of this large group of Western Siberia population, denoted by the common ethnonym ‘Tatars’. It is shown that the Turkic-Tatar population of the Tomsk province was characterized by the heterogeneity of its composition. It is noted that the complexity of the ethnic picture in the Tomsk province was determined by the diversity of the indigenous Turkic population. It is emphasized that over 90 thousand people indicated Tatar as their native language, but not all of them subsequently became part of the emerging Tatar community. It was revealed that the Tatars of the Tomsk province, as well as the Tatar community of Western Siberia as a whole, were characterized by a weak involvement in the all-Russian economic processes.